2008
DOI: 10.1063/1.2953800
|View full text |Cite
|
Sign up to set email alerts
|

X-pinch x-ray sources driven by a 1μs capacitor discharge

Abstract: X pinches formed from tungsten, molybdenum, titanium, aluminum, and alloys, such as constantan and nichrome with diameters of 13–25μm, have been imploded with a 300kA, 1μs quarter-period capacitor discharge and observed with an array of diagnostics including time-integrated optical photography, x-ray pinhole cameras, x-ray Si photodiodes, a flat crystal spectrograph, and a Nd:YAG laser interferometry/schlieren system. The results of these comprehensive observations are presented. When a single, central hot spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Early Х-pinch experiments with the use of current sources on the basis of capacitor batteries [52,64] were not successful because of the too low current rise rate. However, the development of low-inductance capacitors and commutators made it possible to create compact simple-design current sources efficiently used for Х-pinch experiments.…”
Section: Current Generators Used For х-Pinch Experimentsmentioning
confidence: 99%
“…Early Х-pinch experiments with the use of current sources on the basis of capacitor batteries [52,64] were not successful because of the too low current rise rate. However, the development of low-inductance capacitors and commutators made it possible to create compact simple-design current sources efficiently used for Х-pinch experiments.…”
Section: Current Generators Used For х-Pinch Experimentsmentioning
confidence: 99%
“…In addition to directly backlighting wire arrays [578] the X-pinch has been used by Bott et al [579] to diagnose the low density foam on the axis of a wire array. Appartaim and Maakuu [580] have shown that successful X-pinches can also be produced with a more conventional long pulse (∼1 µs quarter period) capacitor bank. With the right choice of wire material and x-ray filter, highly localized bright spots suitable for point-projection radiography can be produced.…”
Section: X-pinchmentioning
confidence: 99%
“…When the current flows through the diode, a hot dense plasma intensely generating soft X ray (SXR) emission forms in the crossing region of the load. Standard X pinches have been studied in detail and were shown to operate quite well at currents from 100 to 500 kA [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%